The policy and practice of implementing a student-athlete support network: a case study - Ryan, C.; Thorpe, H.; Pope, C. (International Journal of Sport Policy and Politics, 2017)
In an effort to address difficulties experienced by elite athletes wanting to pursue tertiary education High Performance Sport New Zealand initiated the `Athlete Friendly Tertiary Network` (AFTN) in 2010. Whilst a number of tertiary institutions across New Zealand have since agreed to implement this policy, it is not yet known whether this implementation has actually resulted in these institutions fulfilling its promise to New Zealand`s high-performance athletes. The current research project therefore sheds light on this previously unexplored area using the case study of one New Zealand University. Framed within interpretive phenomenology, and drawing upon interviews conducted with current elite athletes, this study examines the lived experiences of this university`s high-performance student-athletes and questions whether the AFTN is in fact assisting these individuals to engage in a student-athlete dual career. Results suggest that despite the implementation of the AFTN policy, these student-athletes still face difficulties in combining both their academic and athletic pursuits. Specifically, whilst all participants acknowledged receiving some form of support to complete their studies alongside their sporting requirements, difficulties resulting from long absences away from their place of study, inflexible sporting demands and a lack of flexible course delivery options compounded athletes` struggles. Additionally, despite the university embracing the guidelines set out by the AFTN policy, an apparent lack of awareness and understanding amongst front-line teaching staff has meant that it is yet to fully meet its obligations under this agreement, thus suggesting the importance of clear policy communication throughout sporting and university infrastructures.